Intra-Coronary Thrombolysis with Streptokinase or Lys-Plasminogen/Urokinase in Acute Myocardial Infarction: Effects on Recanalization and Blood Fibrinolysis - de Prost, D; Guerot, C; Laffay, N; Horellou, M H; Samama, M (Thrombosis and Haemostasis, 1983)
Forty-two patients with total occlusion of a coronary vessel were treated with intracoronary fibrinolytic agents. Four therapeutic protocols were compared: group I received streptokinase (SK) as a continuous infusion; group II and III received SK as a bolus at different doses and group IV received lysplasminogen (Pg) plus urokinase (UK); maximal doses were 350,000 IU of SK and 250,000 IU of UK plus 75 μK of Pg. Thrombolysis was assessed by coronary angiography. Coagulation studies were performed prior to, 15 min and 6 hr after the end of the thrombolytic treatment. Recanalization was achieved in 27 of the 31 SK-treated patients (87%) and in 7 of the 11 Pg-UK- treated patients (63.6%). The recanalization frequency was the same in the three SK-treated groups, even though when SK was administered as a bolus, the dose was significantly less than when administered on a continuous infusion. Although systemic fibrinolysis occurred in all 4 groups of patients, this effect was less pronounced in the UK-treated patients than in the three SK- treated groups. This study also shows that recanalization can be achieved with a dose of SK lower than the anti-SK antibody level. Haemorrhagic side effects were minimal in all patients studied. Severe defibrination is usually considered a risk of haemorrhage. These preliminary results suggest that bolus injection of SK or the use of UK plus lys-Pg can reduce the level of defibrination and thus the haemorrhagic risk.
Keywords: Myocardial infarction; Systemic fibrinolysis; Local thrombolysis; streptokinase; Urokinase; Lys-plasminogen